A Comparison of Security in City and Small-Town Gated Developments in the Western Cape province, South Africa. (March 2022) - Spocter, Manfred
Gated developments are a defining feature of the post-apartheid residential landscape. The fortification practices witnessed in gated developments are part of a wider securitisation of the South African urban- and ruralscapes. This research resides in the ambit of the theory of crime and violence as a precursor to the growth in gated developments. Research on gated developments has tended to focus on their proliferation in larger urban settlements, with scant attention being paid to gated developments in smaller settlements and in rural areas. However, non-metropolitan gated developments are a reality, and they display similar security features as those found in metropolitan areas. This paper compares the security levels of gated developments in a suburb of Cape Town with those in small towns in the Western Cape province. Security features are quantified to determine whether differences in securitisation levels exist between the locales. The gated developments in the city display higher levels of security than those in small towns. However, a closer analysis of small-town gated developments reveals high security levels in towns where tourism is the mainstay of the local economy. As the technology of security migrates from military applications to residential applications, a securified small-town future is a real possibility.